Sintesis Tetraetil Ortosilikat (TEOS) dari Silika Hasil Kalsinasi Sekam Padi - Rahmi, Rahmi; Nizar, Umar Kalmar; Khair, Miftahul; Althof, Hasnah Sausan; Azzahra, Wenalda Hanifah; Beri, Deski (Periodic, 2024)
Indonesia is an agricultural country. Where agriculture makes an important contribution to the economy and the fulfillment of people's basic needs. It is known that every 1 kg of rice produced, is able to produce 0.28 kg of rice husk. Rice husk is an agricultural waste that is abundant in nature. In this research, the effect of calcination time on silica obtained from rice husk has been determined. The purity level of the extracted silica is 99%. Silica that has been successfully extracted is then used in the TEOS synthesis process by varying the reaction time. A total of 1 mole of ethanol (58.4 ml) and 0.25 ml (7 grams) of silica powder were added to 250 ml neck flask 3 and the addition of alumnia catalyst as much as 1 gram, then the mixture was refluxed using 800C for 5, 7, 10, 15 and 20 hours. The TEOS obtained was then subjected to several parameter tests that provide information about the physical and chemical conditions, so that this can provide information regarding the quality of the resulting solution. The measurements carried out are, Densiats solution testing, Viscosity and refractive index. From the data obtained the density value of TEOS is 0.986 g/ml - 0.995 g/ml, the viscosity value of TEOS is 0.8176 cps - 0.9337 cps and the refractive index value of TEOS is 1.356 - 1.360. While the yield obtained is from 82.11% - 54.74%.